Prey consumption rates and growth of piscivorous brown trout in a subarctic watercourse - Jensen, Hallvard; Amundsen, Per-Arne; Elliott, J. Malcolm; Bøhn, Thomas; Aspholm, Paul Eric (Journal of Fish Biology, 2006)
This is the peer reviewed version of the following article: Jensen, H., Amundsen, P.-A., Elliott, J.M., Bøhn, T. & Aspholm, P.E. (2006). Prey consumption rates and growth of piscivorous brown trout in a subarctic watercourse. Journal of Fish Biology, 68 (3), 838-848, which has been published in final form at https://doi.org/10.1111/j.0022-1112.2006.00972.x . This article may be used for non-commercial purposes in accordance with Wiley Terms and Conditions for Use of Self-Archived Versions . Prey consumption rates of piscivorous brown trout Salmo trutta were studied in the Pasvik watercourse, which forms the border between Norway and Russia. Estimates of food consumption in the field were similar to or slightly less than maximum values from a bioenergetic model. The piscivore diet consisted mainly of vendace Coregonus albula with a smaller number of whitefish Coregonus lavaretus . Individual brown trout had an estimated mean daily intake of c . 1·5 vendace and 0·4 whitefish, and a rapid annual growth increment of 7–8 cm year −1 . The total population of brown trout >25 cm total length was estimated as 8445 individuals (0·6 individuals ha −1 ), giving a mean ± s.e. annual consumption of 1553880 ± 405360 vendace and 439140 ± 287130 whitefish for the whole watercourse. The rapid growth in summer of brown trout >25 cm indicated a high prey consumption rate.